The study of Yanshanian unconformity tectonic events in Northern Junggar Basin. (October 2019) - Li, Zhenhua; Chen, Zhanjun; Cao, Feng; Zhang, Suya; Huang, Nana
Abstract: Based on the background of Yanshanian tectonic activity in the northern Junggar basin, the temporal and spatial distribution characteristics of Yanshanian unconformity events in the northern Junggar basin are systematically studied through interpretation and comparison of outcrop profiles and seismic profiles. The study shows that Yanshanian stratigraphic unconformity in the northern part of Junggar Basin mainly manifests in the angle unconformity between Xishanyao formation and Toutunhe formation, Toutunhe formation and Tugulu group, which indicates that the study area mainly experienced three important periods of unconformity: the end of Xishanyao formation in middle Jurassic, the end of Toutunhe formation and the end of Tugulu group in early Cretaceous. From the analysis of the unconformity structure and its regional distribution characteristics, it can be concluded that the most prominent Yanshanian tectonic unconformity events occurred mainly in the late Jurassic and showed the unconformity distribution characteristics of the weak compression fold deformation under the background of strike-slip uplift.